AMINO-N-(3-(DIMETHYLAMINO)PROPYL)ACETAMIDEAS AN ABSORBENT FOR CARBON DIOXIDE CAPTURE AND UTILIZATION - MOHAMED MOHSIN, HANAN (2020)
Monoethanolamine (MEA) is a conventional absorbent used for CO2 capture in the industry. However, MEA has limited CO2 absorption capacity. Moreover, high energy input is required to separate CO2 from MEA after the absorption process. In this study, the CO2 desorption process was eliminated through integration of CO2 capture and utilization. The high energy requirement during CO2 utilization can also be reduced through the integration process. The performance of 3-dimethylaminopropylamine (DMAPA) neutralized with glycine as potential absorbent for CO2 capture was evaluated in this study by measuring the CO2 loading capacity of the absorbent. The physical properties of the absorbent were evaluated by measuring the density, viscosity, refractive index, and surface tension of the absorbent